ENGLISH EDUCATION IN INDONESIAN ELEMENTARY SCHOOLS: THE PROFILE, THE STUDENTS' ENGLISH PROFICIENCY, AND THE PEDAGOGICAL PRACTICES - Meisani, Diah Royani (2020)
The resurgence of interest in teaching English for young learners (TEYL) has prosperously grown within Indonesian society as the impact of the spread of the English language for global communication. Despite the challenges, the response to the ever-increasing demand for English has led a vast majority of elementary schools in the country to offer the subject from the first grade of schooling. However, the drastic shift that occurred in the national curriculum influenced its implementation, which the present study investigated. The research began by exploring the current practices of TEYL in a selected Indonesian municipality. It continued with an analysis of factors that should contribute to students' English proficiency levels to find out effective TEYL practices. Through the analysis of multiple regression and ANOVA, four factors were found to contribute to students' English proficiency levels. They were school accreditation, teacher educational background, student's gender and grade level. Employing the participant selection model, a variant of explanatory design in the mixed method, the data were gathered through questionnaires, tests, interviews, focus group discussions (FGD), classroom observations, and documentary checking. The findings revealed that most of the elementary schools in the research site offered English subjects. It was taught in a modest amount of time as an extracurricular by either certified English teachers or the homeroom teachers who did not have an English Education background. The English test results discovered four contributing factors to students' English proficiency levels, including school accreditation, teacher education (TED), students' gender, and grade. Three aspects were found to be the enabling factors to effective pedagogical practices, namely teacher's self-initiated professional development (PD), school English curriculum, and school-university partnerships. Finally, the study proposes four major recommendations concerning the policy of TEYL, the minimum level of English proficiency that English primary teachers should fulfill, better mechanisms and procedures of TED, and the Professional Development School (PDS).